The epicardial electrogram: a quantitative assessment during balloon angioplasty incorporating monophasic action potential recordings. Issue 5 (November 1989) - Taggart, P; Sutton, P; John, R; Hayward, R; Swanton, H
Abstract : An electrogram was recorded from the angioplasty catheter guide wire when coronary blood flow was interrupted in 20 patients undergoing percutaneous transluminal coronary angioplasty. Monophasic action potentials were recorded from the right ventricular septum together with the routine electrocardiogram. The patients were studied during angioplasty for lesions in the left anterior descending (12), circumflex (3), and right coronary arteries (6). ST elevation in the electrogram recorded in the left anterior descending and circumflex systems was usually more obvious than that in the electrocardiogram. Signals obtained from the right coronary artery were of very low amplitude and registered only minimal ST changes. The ST elevation developed in the electrogram during insertion of the catheter before inflation of the balloon in 11 of the 15 patients undergoing angioplasty of the left system. In eight of the patients showing pre-inflation ST elevation the ST shift lessened after successive inflations. Monophasic action potential recordings were obtained during 45 balloon inflations in 19 patients. In those patients undergoing angioplasty for lesions of the circumflex coronary artery the monophasic action potential showed no change during balloon inflation. In patients undergoing angioplasty for the right coronary artery the mean normalised duration at 60 seconds' occlusion was 99.6 (1.5)% of control. Of a total of 25 occlusions in the patients undergoing angioplasty for the left anterior descending coronary artery 19 showed shortening of less than 5%, five showed shortening between 5 and 10%, and one showed a shortening of 16.4% in the monophasic action potential. The QT interval was satisfactorily measured in the electrogram during 36 balloon inflations, and in 24 of these it was also measured in the electrocardiogram. QT changes in the electrogram tended to be the opposite of those in the electrocardiogram. When changes in RR interval were minimal (less than 20 ms) during the balloon inflation 14 of 17 electrograms showed QT prolongation but only one of 12 electrocardiograms showed prolongation. Conversely one of 17 electrograms showed shortening compared with eight of 12 electrocardiograms. There was angiographic evidence of the development of collaterals in six of 15 patients undergoing angioplasty of the left system. ST segment elevation in both the electrogram and electrocardiogram was less pronounced in these patients than in those without evidence of the development of collaterals. ST segment changes recorded from the angioplasty guide wire provide a more sensitive index of ischaemia than the surface 12 lead electrocardiogram, and fall in ST segments on balloon deflation is a prognostic index of a good angiographic result in the left anterior descending and circumflex arteries, but not in the right coronary artery.